Impact of dementia literacy interventions for non-health-professionals: systematic review and meta-analysis. (4th March 2022) - Nguyen, Hoang; Phan, Hoang T; Terry, Daniel; Doherty, Kathleen; McInerney, Fran
Abstract: Objectives: To assess evidence regarding the effects of interventions aimed at improving dementia literacy for different groups of non-health-professionals. Methods: A systematic search for relevant interventions was conducted using a range of online databases (e.g. CINAHL, Embase, Medline, ProQuest, and PsycINFO) and hand-searching of reference lists. Eligible interventions were identified based on predefined inclusion/exclusion criteria and methodological quality criteria. Meta analyses were performed using a random-effects model. Results: The final review included 14 interventions, which were either randomised controlled trials or non-randomised controlled trials. The interventions had varied contents, approaches, settings, and outcome measures. Evidence of improved dementia literacy in various aspects was found, and the intervention effects were strongest on knowledge of dementia. Discussion: There is evidence for the positive impact of dementia literacy interventions on different groups of non-health-professionals. Best practices in intervention contents, approaches, and outcome measures should be examined to guide future interventions.